Fungsi Dana Desa Dalam Pembangunan Desa Tertinggal - Serly Serly; Seli Rosiani; Dwi Intan Pertiwi; M. Deva Septama (Student Research Journal, 2023)
Village Funds provide a very strategic position for villages. With the existence of very large Village Funds, village governments are required to manage village finances wisely. In accordance with Law Number 6 of 2014 concerning Villages which explains that village financial management must fulfill the principles of accountability, transparency, participation and be carried out in an orderly and disciplined manner. budget. The aim of this research is to describe the use of Village Funds in village development and empowering village communities. Village Funds are funds sourced from the APBN which are transferred through the City Regency APBD which are prioritized to finance government administration, village development and village community empowerment. Village Funds with the aim of describing the accountability of Village Fund management which obtains the number of Village Funds and the number of communities depending on the geographical location of each different village. It is also supported by good community participation in carrying out village development. However, in reality there are still several villages whose administration is still not good, this is because human resources in these villages are inadequate. From these results, it still requires ongoing human resource competency development and assistance from local government officials.